Can definitive chemoradiation offer a cure along with cosmesis in locally advanced IVA carcinoma buccal mucosa? a case report - Sharma, Jyoti; Gupta, Manish; Siddharth Vats; Negi, Naina (International Journal of Clinical Trials, 2023)
Surgery is the mainstay of the treatment in ca buccal mucosa. It is extensive in nature and may require efficient reconstruction for good cosmetic outcome. Adjuvant radiation or chemo-radiation may be needed in advanced cancers. Definitive chemoradiation or palliative radiation are reserved for inoperable patients. We present a case report of advanced carcinoma of oral cavity in the left buccal mucosa along with involvement of retromolar trigone along with bone involvement in left sided mandible who opted out for undergoing definitive surgery. She was treated with definitive chemoradiation with 2.4 Gy per day /0.4 Gy in morning, 2 Gy in evening five days a week along with paclitaxel on Sunday. Patient reported after seven years disease free with excellent cosmetic outcome. Definitive surgery along with adjuvant radiation or chemoradiation is the standard of care in advanced cancers of buccal mucosa. However, in inoperable patients or the patients refusing surgery definitive chemoradiation with altered fractionation schedules may still offer a chance of cure and good cosmesis.